2022
DOI: 10.1155/2022/9244500
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Drug Resistance by Furanochromones in NorA Overexpressing Staphylococcus Aureus

Abstract: Khellin and visnagin are natural furanochromones that photoreact with DNA. Khellin has been used in the treatment of vitiligo and psoriasis, as well as in the treatment of angina pectoris and asthma due to its potent action as a coronary vasodilator and antispasmodic agent. The present study aimed to investigate whether the compounds khellin and visnagin act as inhibitors of NorA protein, an efflux pump overproduced by the strain of Staphylococcus aureus SA-1199B that confers resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…33 However, visnagin has also been reported to bind human cyclooxygenase-2 (COX-2), an enzyme not found in plants, 34 and in silico binding studies have also reported that khellin and visnagin bind still other human and bacterial proteins. 35,36 Our earlier work of the physiological effects of khellin and visnagin on plants led us to conclude that these compounds may have a complex mode of action, involving more than one molecular target. 8 Considering the number of mammalian proteins with which these compounds interact, this seems highly possible, making the use of binding studies with only one target protein less useful in optimizing the effect of these compounds as a herbicide.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…33 However, visnagin has also been reported to bind human cyclooxygenase-2 (COX-2), an enzyme not found in plants, 34 and in silico binding studies have also reported that khellin and visnagin bind still other human and bacterial proteins. 35,36 Our earlier work of the physiological effects of khellin and visnagin on plants led us to conclude that these compounds may have a complex mode of action, involving more than one molecular target. 8 Considering the number of mammalian proteins with which these compounds interact, this seems highly possible, making the use of binding studies with only one target protein less useful in optimizing the effect of these compounds as a herbicide.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…With the NorA efflux pump, osthol potentiated the antibiotic activity against S. aureus 1199B and had in silico affinity with the protein, highlighting the hydrophobic interactions and hydrogen bonds, for example, with Arg98, as occurred with coumarin C2 [38]. Furanochromones are compounds structurally similar to coumarins, and the study by Rodrigues et al [39] showed that khellin, like C1, interacts with the NorA model through hydrophobic interactions with Phe16 and Ile136. The amino acids Arg310, Asn340, Gln51, Met109, Ser333, and Ser337 also appear in both studies but are involved in different types of interactions.…”
Section: Discussionmentioning
confidence: 97%
“…π-sulfur interaction (CPZ), carbon-hydrogen bonds (including with serine), and van der Waals interactions were also identified. Other amino acids, such as Ala48, Arg310, and Asn340, for example, are targets of EPIs and coumarins, but with different interactions [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The docking study revealed that the molecule interacted with the NorA efflux pump's Ser-218, Ile-135, Thr-335, and Asn-339 residues [131]. Thiophene, a curcuminoid, showed competitive inhibition against norfloxacin, and formed an H bond with the Arg-310 residue of NorA [132]. The furanochromones khellin and visnagin showed EPI activity by interacting with the Arg-310 residue of the NorA efflux pump, resulting in a two-fold reduction in the MIC of norfloxacin [132].…”
Section: Competitive and Non-competitive Inhibition By Epismentioning
confidence: 99%